EFEKTIFITAS METODE PROBLEM SOLVING DALAM LAYANAN INFORMASI OLEH GURU BK DI KELAS VIII SMP N 6 SAWAHLUNTO - Putri, Rintan Dwina; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2014)
This research pursuant to finding of two method in execution of information service in researcher place school execute practice experience of tuition field of konseling go to school and educational of year 2012 that is method deliver a lecture and method of problem solving. From both that method of researcher wish to check effective how execution of information service conducted with method of problem solving. The result of this research are to describe 1) effective method of problem solving in execution of information service seen from cognate aspect 2) effective method of problem solving, in execution service seen from aspect of afective. Population in this research is educative participant which get information service by using method of problem solving counted 30 people. Instrument is used in this research is enquette. While data analysis used by percentage technique. Result of this research lay open that 1) efective method of problem solving in information service seen from cognate aspect pertained at effective category 2) efective method of problem solving in information service pursuant to aspect of afective pertained at effective category, this matter seen from knowing and information service application with method of problem solving.